Research on inter-blockchain service framework and communication mechanism based on smart service transaction - Bohan KANG; Ning ZHANG; Jianming ZHU (网络与信息安全学报)
Due to the lack of communication mechanism between inter-blockchain services, it is difficult to formulate effective interconnection between different blockchain.Under the smart services ecosystem, two parties of the transaction not only execute the single transaction of data assets, but also extend the scope of their services to cover a wider range of digital assets transfer scenarios.An inter-blockchain communication(IBC) framework for smart service transaction is designed.With component-based and modular design, it makes flexible for the subject and object application of smart service transaction to access IBC framework and thus promote inter-blockchain scalability.Finally, a three-phrase inter-blockchain communication protocol for smart service transaction is proposed to ensure the atomicity and consistency of inter-blockchain ecosystem.